2020
DOI: 10.5902/2236499461324
|View full text |Cite
|
Sign up to set email alerts
|

Análise da disponibilidade de imagens Landsat e Sentinel para o Brasil

Abstract: Neste trabalho, analisamos a disponibilidade de dados sem nuvens dos programas Landsat (refletância da superfície, 1982-2019) e Sentinel 2 (reflectância no topo da atmosfera, 2015-2019) no território brasileiro. No caso do Landsat, a quantidade de informações disponíveis aumenta consideravelmente em 1999 com o início do Landsat 7. No entanto, principalmente devido à presença de nuvens, a disponibilidade de dados varia muito em espaço e tempo. O bioma Amazônia, em particular, apresenta escassez de dados com uma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
0
0
1
Order By: Relevance
“…It is worth noting that in the range 0 • -10 • south latitude, especially in the summer and autumn, there is a high rainfall and high clouds presence [21]. In a previous study, we assessed the availability of Landsat images during the period 1984-2019 and found that the number of valid data was low in some Brazilian biomes such Amazonia (tropical rain forests) and Caatinga (mosaic deciduous woody formations) due to clouds presence [22].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that in the range 0 • -10 • south latitude, especially in the summer and autumn, there is a high rainfall and high clouds presence [21]. In a previous study, we assessed the availability of Landsat images during the period 1984-2019 and found that the number of valid data was low in some Brazilian biomes such Amazonia (tropical rain forests) and Caatinga (mosaic deciduous woody formations) due to clouds presence [22].…”
Section: Introductionmentioning
confidence: 99%
“…Destaca-se que esta coleção é a mais recomendada para análises de séries temporais (MAS et al, 2020). As variações causadas pela fenologia ou mudanças na geometria solar, são minimizadas pelas correções de reflectância e sombra de nuvem.…”
Section: Histórico Do Comportamento Espectral Da Vegetaçãounclassified